Adults living with a diagnosis of ADHD or ASD: Different diagnoses, yet similar personal impacts? - Walsh, Irene (My University, 2018)
The aim of this study is to provide greater insight into the phenomenon of living with ADHD and/or ASD in adulthood, as directly reported by those who experience the conditions. And, to explore how a late diagnosis, attitudes of others, and social communication challenges may impact sense of self, wellbeing, and identity.
Revolutionary Learning, Evolutionary Practice 2018 ASHA Convention
Keywords: Mental Health; ADHD; ASD; Wellbeing; Identities in Transformation; Inclusive Society; Mental Health (Dis-)order; Autistic Spectrum disorders; Mental Health/Psychosocial disability